Upaya Meningkatkan Hasil Belajar Matematika Melalui Metode Bermain Anak Tangga - Wahyu Rokhati (Academy of Education Journal, 2019)
The background of this research was carried out because of the low activeness and learning outcomes of students in class III about the measurement of long units motivating the activeness and student learning outcomes of mathematics in Basic Competencies Using Measuring Tools in Problem Solving. This research is a Classroom Action Research with the subjects of third grade students of SD Negeri 1 Karanganyar with a total of 19 students. Data sources come from documents, students, and peers. Data collection techniques with test and non-test. The research process was carried out in two cycles, each cycle consisting of 2 meetings each meeting 2 lesson hours. To measure the ability of students in mastering the material that has been given, each end of the cycle carried out an evaluation. The results obtained from the data there is an increase in learning outcomes seen from the initial study before the action and after the action. The data about the learning outcomes obtained are as follows: the average grade of the class in the initial study was 53 with 21% mastery learning; the average value of cycle 1 is 61 with a 42% mastery learning; the average value of the second cycle is 72.5 with 95% mastery learning. It can be concluded that the use of the ladder playing method can increase the activeness and learning outcomes of students, especially the Long Unit Measurement material.